Sensitized thulium blue and red upconversion emission and energy-transfer processes in Nd3+/Yb3+/Tm3+-codoped PbGeO3-based glass excited around 800 nm - Gouveia-Neto, A. S.; Dos Santos, P. V.; Bueno, L. [UNESP]; Ribeiro, S. J.L. [UNESP]; Messaddeq, Y. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2003)
This paper reports on the generation of bright blue and red upconversion luminescence through the sensitization of thulium ions in Nd3+Yb3+Tm3+ triply-doped 70%XoPbGeO3:15%PbF2:15%CdF2-glass excited by a diode laser source around 800 nm. The upconversion fluorescence spectra of Tm3+ ions under 800 nm excitation is presented, for a sample codoped with Yb and a Nd3+Yb3+Tm3+ triply-doped sample. It is observed that the presence of Nd3+ in the system, produces a tenfold enhancement in the blue emission associated to the 1G4 - 3H6 transition of Tm3+ ions, as compared to samples doped with Tm3+Yb3+. The dependence of the upconversion emission intensity as a function of the excitation power was examined and a quadratic power law behavior was obtained indicating the participation of two pump photons in the upconversion excitation mechanism. The upconversion excitation process of the Tm3+ ion 1G4 emitting level was achieved by an initial energy-transfer process from the 800 nm excited Nd3+ to Yb3+. The excited Yb3+ then, transfer its energy to a Tm3+ ion at the 3H4 level excited by a pump photon at 800 nm.